Promotion of partial nitritation-anammox process by improving granule proportion - Cheng, Jun (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
For enhancing the partial nitritation-anammox (PN/A) process, the effects of granule fraction on system performance were investigated in this study. Two sequencing batch reactors (SBRs) were inoculated with PN/A biomass with a floc mass fraction of 53%. In SBR1, when the nitrogen removal rate (NRR) was stable, flocculent sludge was gradually discharged from the reactor using a screen, and the granule fraction was therefore increased. However, nitrogen removal was not improved and finally deteriorated due to the loss of nitritation activity. In SBR2, most flocculent sludge was eliminated and granular proportion was maintained at over 90% by controlling a short settling and decanting time. NRR was low initially but gradually improved to 1.23 kg N/(m3·d), which was 54% higher than SBR1. Ammonium oxidation activities of flocs and granules were respectively measured. Results suggested that the increase of nitritation activity in the granules was the main reason for the improvement of nitrogen removal in SBR2